PENSION REFORM IN INDIA WITH REFERENCE OF NEW PENSION SCHEME - KALI, SUKHEN; JANA, SUBRATA (IJRDO - Journal of Business Management, 2017)
With the introduction of new pension system, government is now trying to provide adequate retirement income not only to the government employees but also to all citizens of India. The Government employees (except the employees of Armed Forces) who have already joined the service on or after 01.01.2004 covered under the New Pension scheme (NPS). In this Scheme, pension will be determined totally on the return of the pension fund at the time of the retirement. The second phase of NPS is being introduced in India from 01.04.2009 for non-government employees. This paper aims to point out the different aspects of pension benefits available under the traditional old pension system (OPS) and under the new pension system (NPS) and also mechanism, performance of New Pension Scheme. An attempt has been made to provide a brief idea about the pension benefits under the Old Pension Scheme and New Pension Scheme of the government employees of different cadres i.e. Cadre A, B, C and D.